Organization of Conferences in the Classroom: Faculty Innovation and University Social Commitment - Ruiz-Bejarano, Aurora María (2018)
This article presents an experience carried out at Universidad de Cadiz, which was part of the 2017/2018 call for proposals for Guaranteed Interventions for Teaching Improvements of said university where the project “The student body and the production of knowledge. Organization of conferences on childhood, citizenship, and school.” was approved. The project aims to raise awareness among university students about the needs, rights, and responsibilities of childhood, through the teaching and learning processes taking place in the classroom. Additionally, in the area of University Social Responsibility, it aims to introduce students to one of the paths offered by the University to intervene in matters related to childhood: the organization of conferences on citizenship, childhood, and education for peace and non-violence. This way, the project represents a teaching innovation strategy that relates transfer of knowledge, the academic ethical dimension, and university social commitment. This article presents the organizational structure of the proposal in a Childhood Education undergraduate program classroom.